2015
DOI: 10.1161/strokeaha.115.009913
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Particulate Matter Air Pollution Is a Risk Factor for Stroke

Abstract: Background and Purpose— Epidemiological studies suggest an association between stroke incidence and stroke mortality and long-term exposure to particulate matter (PM) air pollution. However, the magnitude of the association is still unclear. Methods— We searched the Pubmed citation database for epidemiological studies and reviews on stroke and PM exposure. Then, we carried out a meta-analysis to quantify the pooled association between str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(90 citation statements)
references
References 48 publications
4
79
1
6
Order By: Relevance
“…184 Meta-analyses have found a consistent positive association between air pollution and stroke; an analysis of 20 studies identified that exposure to a 5-ug/m 3 increase in PM 2.5 increases the risk of a stroke by 6% and stroke mortality by 12.5%. 185 …”
Section: Stroke Risk Factorsmentioning
confidence: 99%
“…184 Meta-analyses have found a consistent positive association between air pollution and stroke; an analysis of 20 studies identified that exposure to a 5-ug/m 3 increase in PM 2.5 increases the risk of a stroke by 6% and stroke mortality by 12.5%. 185 …”
Section: Stroke Risk Factorsmentioning
confidence: 99%
“…Liang and his colleagues conducted a systematic review to report the significant impact of PM 2.5 exposure on blood pressure, with the strongest association for the long-term exposure [6]. A meta-analysis study further showed the scientific evidence that long-term exposure to particulate matter with dynamic diameter less than 10 μm (PM 10 ) is regarded as a risk factor of stroke [7]. Mannsaker et al reported that exposure to nitric oxide (NO) and nitrogen dioxides (NO 2 ) may influence the hospitalizations for cardiovascular disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has also suggested that ambient particles may have aging-related effects: particulate matter with aerodynamic diameter ≤ 2.5 µm (PM 2.5 ) exposures have been associated with age-related outcomes including brain atrophy [2], declines in cognitive performance [3], ischemic heart disease [4], and stroke [5], as well as increases in systolic blood pressure by as much as 4.6 mmHg [6, 7]. Moreover, traffic related particle exposures have been associated with hastened lung function decline by 6–7% over a five year period [8], accelerated pigment spot formation, and other clinical hallmarks of premature skin aging [9].…”
Section: Introductionmentioning
confidence: 99%